Unique factors to the implementation of a disaster preparedness plan at Georgetown Public Hospital in Guyana. Issue 4 (April 2021) - Van Meter, Jessica; Lauderdale, Jana; Rohde, John Paul
Abstract : Abstract: Disaster planning in developing countries is largely ineffective despite these countries being more likely to suffer from catastrophic events. This article aims to identify strengths, educational needs, practice improvement opportunities, and local factors that may contribute to the development/implementation of a disaster preparedness plan at Georgetown Public Hospital in Guyana. Abstract : This article aims to identify strengths, educational needs, practice improvement opportunities, and local factors that may contribute to the development/implementation of a disaster preparedness plan at Georgetown Public Hospital in Guyana.